Influence of Age and Number of Seedlings on Yield and Nutrient Uptake by Machine Transplanted Rice (Oryza sativa L.) - Negalur, R. B.; Halepyati, A. S.; Rao, K. Narayana (International Journal of Bio-resource and Stress Management, 2023)
The field experiments were conducted at Agricultural Research Station, Gangavathi, University of Agricultural Sciences, Raichur, Karnataka during kharif, 2012 and 2013 to study the effect of different age and number of seedlings hill-1 on nutrient uptake, availability and yield of machine transplanted rice. Pooled mean indicated that, planting of twenty five days old seedlings recorded significantly higher uptake of nitrogen by grain (68.06 kg ha-1), straw (47.46 kg ha-1) and total nitrogen uptake by the plant (115.52 kg ha-1) uptake of phosphorous by grain (26.06 kg ha-1), straw (13.20 kg ha-1) and total phosphorous uptake by the plant (37.26 kg ha-1), uptake of potash by grain (20.66 kg ha-1), straw (57.19 kg ha-1) and total potash uptake by the plant (77.85 kg ha-1), available soil nitrogen, phosphorous and potash (236.30, 47.80 and 345.30 kg ha-1, respectively), grain and straw yield (5101 and 6335 kg ha-1, respectively), Likewise planting of 3−4 seedlings recorded significantly higher uptake of nitrogen by grain, straw and total nitrogen uptake by the plant (71.67, 50.96 and 122.63 kg ha-1, respectively), uptake of phosphorous by grain, straw and total phosphorous uptake by the plant (25.31, 13.73 and 39.03 kg ha-1, respectively), uptake of potash by grain, straw and total potash uptake by the plant (21.78, 59.67 and 81.45 kg ha-1, respectively), available soil nitrogen, phosphorous and potash (230.95, 45.35 and 342.95 kg ha-1, respectively), grain and straw yield (5330 and 6585 kg ha-1, respectively).